Implementation of Islamic Parenting in Toba Batak Families - Parinduri, Muhammad Abrar (Universitas Muhammadiyah Magelang, 2022)
The personality of a child is determined by genetic and environmental factors. Parenting style is the first environment that makes a major contribution in shaping a child's personality. This study uses a qualitative descriptive method by collecting data through visits to respondents. Data collection techniques through interviews and documentation. Data analysis techniques include data reduction, data presentation, drawing conclusions and verification. Research shows that parents try to apply Islamic parenting to their children through psychological, mental, faith education, religious enthusiasm, moral and social education. Includes honesty, treating children fairly, and beauty education. Factors that support parents are able to apply success in Islamic parenting with motivation from parents, living environment, and parental education. The inhibiting factors for parents in applying Islamic parenting to their children are due to the busyness of the parents, socioeconomic conditions, and the parenting model that parents get from birth.